Dephosphorylation of the Core Septin, AspB, in a Protein Phosphatase 2A-Dependent Manner Impacts Its Localization and Function in the Fungal Pathogen Aspergillus fumigatus - Vargas-Muñiz, José M.; Renshaw, Hilary; Richards, Amber D.; Waitt, Greg; Soderblom, Erik J.; Moseley, Martin. A.; Asfaw, Yohannes; Juvvadi, Praveen R.; Steinbach, William J. (Frontiers in Microbiology, 2016)
Septins are a conserved family of GTPases that form hetero-oligomeric complexes and perform diverse functions in higher eukaryotes, excluding plants. Our previous studies in the human fungal pathogen Aspergillus fumigatus revealed that the core septin, AspB, a CDC3 ortholog, is required for septation, conidiation, and conidial cell wall organization. Although AspB is important for these cellular functions, nothing is known about the role of kinases or phosphatases in the posttranslational regulation and localization of septins in A. fumigatus. In this study, we assessed the function of the Gin4 and Cla4 kinases and the PP2A regulatory subunit ParA, in the regulation of AspB using genetic and phosphoproteomic approaches. Gene deletion analyses revealed that Cla4 and ParA are indispensable for hyphal extension, and Gin4, Cla4, and ParA are each required for conidiation and normal septation. While deletion of gin4 resulted in larger interseptal distances and hypervirulence, a phenotype mimicking aspB deletion, deletion of cla4 and parA caused hyperseptation without impacting virulence, indicating divergent roles in regulating septation. Phosphoproteomic analyses revealed that AspB is phosphorylated at 5 residues in the GTPase domain (S134, S137, S247, T297 and T301) and 2 residues at its C-terminus (S416 and S461) in the wild-type, Δgin4 and Δcla4 strains. However, concomitant with the differential localization pattern of AspB and hyperseptation in the ΔparA strain, AspB remained phosphorylated at 2 additional residues, T68 in the N-terminal polybasic region and S447 in the coiled-coil domain. Generation of nonphosphorylatable and phosphomimetic strains surrounding each differentially phosphorylated residue revealed that only AspBmt-T68E showed increased interseptal distances, suggesting that dephosphorylation of T68 is important for proper septation. This study highlights the importance of septin phosphorylation/dephosphorylation in the regulation of A. fumigatus hyphal septation.